Response of Tonsil Follicular Dendritic Cell Sarcoma to Multimodal Treatment Including Pembrolizumab: A Case Report and Literature Review - Chen, Nanxiang; Ba, Wei; Zhao, Dawei; Sheng, Lei; Zhang, Xinxin (Frontiers in Oncology, 2022)
Follicular dendritic cell sarcoma (FDCS) is a rare malignant neoplasm that was classified by the World Health Organization (WHO) under histiocytic and dendritic cell neoplasms in the 2016 revision. Considering the rarity of this tumor, there is no standardized treatment. It is usually treated by complete surgical resection. Adjuvant chemotherapy and radiotherapy are alternative methods. Immune checkpoint inhibitors (ICIs) represented by the programmed death receptor 1/programmed death ligand 1 (PD-1/PD-L1) antibody have achieved significant clinical benefits in a variety of solid tumors. However, reports on the treatment of FDCS with ICIs are rare. FDCS often expresses high levels of PD-L1, which provides a rationale to use immunotherapy in cases of FDCS. Here, we present a 51-year-old Filipino-Chinese man with FDCS who was treated with multimodal treatment, including the PD-1 inhibitor pembrolizumab and achieved a relatively long disease-free survival of 24 months. This case emphasizes that the application of ICIs under the guidance of NGS technology seems to be a meaningful treatment option for patients with FDCS.